2016
DOI: 10.1055/s-0036-1571470
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Immunohistochemical Markers p16 and Ki-67 and Their Usefulness in the Diagnosis of Cervical Intraepithelial Neoplasms

Abstract: Our study showed that the agreement among observers using traditional diagnostic criteria of cervical intraepithelial lesions can improve with the use of immunohistochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Overexpression of p16 is commonly found in cells infected by HPV. Currently, IHC expression of p16 together with the expression of Ki-67 is routinely used to improve diagnosis of cervical lesions [14][15][16]. In the present study, the correlation between the grade of cervical lesions and the expression of p16 was strong (p < 0.0001).…”
Section: Discussionsupporting
confidence: 53%
“…Overexpression of p16 is commonly found in cells infected by HPV. Currently, IHC expression of p16 together with the expression of Ki-67 is routinely used to improve diagnosis of cervical lesions [14][15][16]. In the present study, the correlation between the grade of cervical lesions and the expression of p16 was strong (p < 0.0001).…”
Section: Discussionsupporting
confidence: 53%
“…Studies of p16 in HIV-negative women have shown sensitivity from 79–97%, specificity from 71–85%, and PPV from 41–91% [10, 1921]. In our population of HIV-infected women, p16 sensitivity (54%), specificity (72%), and PPV (36%) were lower, irrespective of ART and immune status.…”
Section: Discussionmentioning
confidence: 59%